Differenze tra le versioni di "Algebra vettoriale/Derivazione dei vettori"

<math>{|K_0|d\over dx} \vec{\mathcal{A}}={|K_0|d\over dx}(a_1\vec{\mathcal{e_1}}+a_2\vec{\mathcal{e_2}}+a_3\vec{\mathcal{e_3}})=</math><br>
<math>\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ =(\vec{\mathcal{e_1}}{|K_0|d\over dx} a_1+\vec{\mathcal{e_2}}{|K_0|d\over dx} a_2+\vec{\mathcal{e_3}}{|K_0|d\over dx} a_3)+(a_1{|K_0|d\over dx}\vec{\mathcal{e_1}}+a_2{|K_0|d\over dx}\vec{\mathcal{e_2}}+a_3{|K_0|d\over dx}\vec{\mathcal{e_3}})</math>
 
<math> {|K_0|d\over dx} a_1={|K|\over dx}a_1={d\over dx}a_1</math>
 
<math>\vec{\mathcal{e_1}} {|K_0|d\over dx} a_1=\vec{\mathcal{e_1}}{|K|\over dx}a_1={|K|d\over dx}(a_1 \vec{\mathcal{e_1}})</math>
 
 
<math>\vec{\mathcal{e_2}}{|K_0|d\over dx} a_2={|K|d\over dx}(a_2 \vec{\mathcal{e_2}})</math>
 
 
 
 
 
 
<math> (K_0){d|K_d|\over dx} f(x)</math>